Engagement in physical education classes and health among young people: does sports practice matter? A cross-sectional study - Coledam, Diogo Henrique Constantino; Ferraiol, Philippe Fanelli (São Paulo Medical Journal, 2017)
CONTEXT AND OBJECTIVE: Physical education classes aim to promote health but it is unknown whether benefits occur independently of sports practice. The purpose of this study was to examine associations between engagement in physical education classes and physical fitness and obesity according to sports practice among Brazilian students. DESIGN AND SETTING: Cross-sectional school-based study involving 737 students aged 10-17 years in southern Brazil. METHODS: Engagement in physical education classes and sports practice were analyzed using a self-report questionnaire. The health indicators analyzed were cardiorespiratory fitness, muscle strength, obesity and combinations thereof. The covariates were sex, age, socioeconomic status, physical activity and sedentary behavior. Prevalence ratios (PR) adjusted for confounding variables were estimated using Poisson regression. Analyses were stratified according to sports practice. RESULTS: Engagement in physical education classes was associated with achievement to health-related criteria for cardiorespiratory fitness (PR = 1.52), muscle strength (PR = 1.55), obesity + cardiorespiratory fitness (PR = 1.51), obesity + muscle strength (PR = 1.70), cardiorespiratory fitness + muscle strength (PR = 2.60) and the three outcomes combined (PR = 2.43), only among non-sports practitioners, all P < 0.05. Engagement in physical education classes was not associated with obesity (PR = 1.00, P > 0.05). No associations were found for sports practitioners (P > 0.05). CONCLUSION: Engagement in physical education classes was associated with health among non-sports practitioners. However, to protect students from obesity and promote additional health benefits for sports practitioners, the conventional physical education program offered to the sample studied should be reformulated.